Assessing the effectiveness of a menstrual hygiene management and sexual and reproductive health education program in post-earthquake Nepal - Baumann, Sara E.; Anwer, Hiba; Lhaki, Pema; Burke, Jessica G. (Journal of Health Promotion, 2022)
This study assesses the effectiveness of a menstrual hygiene management (MHM) and sexual and reproductive health (SRH), school-based education program conducted in Dhading, Nepal after the 2015 mega-earthquake. The intervention aimed to improve MHM/SRH knowledge among adolescent girls on a range of topics including adolescence, female anatomy, menstruation, and more. Quantitative data were collected via cross-sectional, self-administered, community-based surveys after the 2015 earthquake with 3,319 adolescent girls in grades 7-9 in Dhading district. Data were collected using the same survey tool before and after the intervention and responses were compared using SAS 9.4. Before the intervention, the median MHM/SRH knowledge score was 50% of the pre-test questions answered correctly. After the intervention, the median MHM/SRH knowledge score improved to 73% of the post-test questions answered correctly. Topics with the greatest percentage improvements between pre- and post-tests included age of menarche (from 20.5% to 60.0%), timing of taking emergency contraceptive pills after unsafe sexual contact (from 14.8% to 54.1%), and approaches for managing menstrual pain (from 42.2% to 77.1%). The school-based MHM/SRH educational intervention led to significant improvements in participant MHM/SRH knowledge. Equipping girls with accurate information about MHM/SRH long before a disaster occurs by embedding the information into the national school curriculum is one way to ensure they are prepared with key information required to manage MHM/SRH needs if another disaster occurs.